Physical effects of playing area and player number during team sport small-sided games - Tyndel, S. (Journal of Australian Strength and Conditioning, 2018)
Small-sided games (SSGs) are widely used during training sessions in different team sports. SSG is the name given to a training drill when played with reduced player number or playing area compared to official competition conditions. Consequently, the purpose of this review was to provide practitioners with a summary of the main physiological and time-motion effects resulting from manipulation of the playing area or player number in SSGs. An extensive literature search was carried out using databases such as PubMed, Scopus, SPORTDiscus, MEDLINE and Google Scholar. 75 SSG articles were examined for the purpose of this review. The optimal physiological stimulus for high-intensity aerobic conditioning (=90% HRmax) is achieved with outfield player numbers below 5 (i.e. 2v2 - 4v4) and a relative playing area of ~ 100-150 m2+ per player. In contrast, large magnitude accelerations/decelerations (=3 m.s-2) and peak sprint velocities occur with greater player numbers (8v8+) and absolute space (200-350 m2 per player). The main limitation with using SSGs is the inability to replicate the high-intensity running and repeated sprint demands of official competition. Conditioning staff should therefore look to supplement SSGs with some traditional running fitness work. There should be a particular emphasis on supra-maximal MAS running intervals (=100%) and maximal sprints in order to expose players to running velocities >19 km/h. This would be particularly relevant for coaches and fitness staff of all team sports played in large playing areas such as the various rugby codes, Australian rules, soccer as well as field hockey.